CD8+ T cells as a source of IFN-γ production in human cutaneous leishmaniasis. - Mahmoud Nateghi Rostami; Hossein Keshavarz; Rosita Edalat; Abdolfattah Sarrafnejad; Tahereh Shahrestani; Fereidoun Mahboudi; Ali Khamesipour (Public Library of Science (PLoS), 2010)
BACKGROUND: In human leishmaniasis Th1/Th2 dichotomy similar to murine model is not clearly defined and surrogate marker(s) of protection is not yet known. In this study, Th1/Th2 cytokines (IL-5, IL-10, IL-13 and IFN-γ) profile induced by purified CD4(+)/CD8(+) T cells in response to Leishmania antigens were assessed at transcript and protein levels in 14 volunteers with a history of self-healing cutaneous leishmaniasis (HCL) and compared with 18 healthy control volunteers. METHODOLOGY/PRINCIPAL FINDINGS: CD4(+)/CD8(+)/CD14(+) cells were purified from peripheral blood using magnetic beads; CD4(+)/CD8(+) T cells were co-cultured with autologous CD14(+) monocytes in the presence of soluble Leishmania antigens (SLA). Stimulation of either CD4(+) T cells or CD8(+) T cells of HCL volunteers with SLA induced a significantly (P<0.05) higher IFN-γ production compared with the cells of controls. Upregulation of IFN-γ gene expression in CD4(+) cells (P<0.001) and CD8(+) cells (P = 0.006) of HCL volunteers was significantly more than that of controls. Significantly (P<0.05) higher fold-expression of IFN-γ gene was seen in CD4(+) cells than in CD8(+) cells. In HCL volunteers a significantly (P = 0.014) higher number of CD4(+) cells were positive for intracellular IFN-γ production than CD8(+) cells. CONCLUSIONS/SIGNIFICANCE: Collectively, the volunteers have shown maintenance of specific long-term immune responses characterized by a strong reaction to leishmanin skin test and IFN-γ production. The dominant IFN-γ response was the result of expansion of both CD4(+) and CD8(+) T cells. The results suggested that immune response in protected individuals with a history of zoonotic cutaneous leishmaniasis (ZCL) due to L. major is mediated not only through the expansion of antigen-specific IFN-γ producing CD4(+) Th1 cells, but also through IFN-γ producing CD8(+) T cells.